Genetic variants in ATP6 and ND3 mitochondrial genes are not associated with aggressive prostate cancer in Mexican–Mestizo men with overweight or obesity. (2nd July 2016) - Canto, Patricia; Benítez Granados, Jesús; Martínez Ramírez, Mónica Adriana; Reyes, Edgardo; Feria-Bernal, Guillermo; García-García, Eduardo; Tejeda, María Elena; Zavala, Esperanza; Tapia, André; Rojano-Mejía, David; Méndez, Juan Pablo
Abstract: Mitochondrial defects have been related to obesity and prostate cancer. We investigated if Mexican–Mestizo men presenting this type of cancer, exhibited somatic mutations of ATP6 and/or ND3 .Body mass index (BMI) was determined; the degree of prostate cancer aggressiveness was demarcated by the Gleason score. DNA from tumor tissue and from blood leukocytes was amplified by the polymerase chain reaction and ATP6 and ND3 were sequenced. We included 77 men: 20 had normal BMI, 38 were overweight and 19 had obesity; ages ranged from 52 to 83. After sequencing ATP6 and ND3, from DNA obtained from leukocytes and tumor tissue, we did not find any somatic mutations. All changes observed, in both genes, were polymorphisms. In ATP6 we identified, in six patients, two non-synonymous nucleotide changes and in ND3 we observed that twelve patients presented non-synonymous polymorphisms. To our knowledge, this constitutes the first report where the complete sequences of the ATP6 and ND3 have been analyzed in Mexican–Mestizo men with prostate cancer and diverse BMI. Our results differ with those reported in Caucasian populations, possibly due to ethnic differences.